PROBLEMATIKA PERATURAN PERUNDANG-UNDANGAN PENDIDIKAN AGAMA DI SEKOLAH - Achmad Habibullah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
AbstractThe main objective of the regulation of religious education with its all types, namely Undang-Undang, Peraturan Pemerintah, Peraturan Menteri and its legal derivations, is of course, to regulate, to order, to direct any educational process will be carried out well and effectively. But, on the contrary, it is often those regulations raised any new problems must be solved. This research aimed at to describe what problems arised as the effect of the implementation of the certain educational regulation regarding with some aspect of educational system. The result of study at those aspect shows the weakness, unsynchronism, and contradiction between one regulation with another regulation related to religious education in school. For this purpose, accordingly, the needs for completion and revision of law and regulation of religious education is something necessary to be realized.